Selective enzymatic esterification of lignin model compounds in the ball mill - Weißbach, Ulla; Dabral, Saumya; Konnert, Laure; Bolm, Carsten; Hernández, José G. (Beilstein Journal of Organic Chemistry, 2017)
A lipase-catalyzed esterification of lignin model compounds in the ball mill was developed combining the advantages of enzyme catalysis and mechanochemistry. Under the described conditions, the primary aliphatic hydroxy groups present in the substrates were selectively modified by the biocatalyst to afford monoesterified products. Amongst the tested lipases, CALB proved to be the most effective biocatalyst for these transformations. Noteworthy, various acyl donors of different chain lengths were tolerated under the mechanochemical conditions.
Keywords: ball milling; enzymes; esterification; lignin derivatization; mechanochemistry

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

(untitled) - Do, J.-L.; Friščić, T. (ACS Cent. Sci., 2017)

Ball Milling Towards Green Synthesis: Applications, Projects, Challenges - Métro, T.-X.; Colacino, E.; Martinez, J.; Lamaty, F. (Amino Acids and Peptides in Ball Milling, 2015)

(untitled) - Rodríguez, B.; Bruckmann, A.; Bolm, C. (Chem. – Eur. J., 2007)

(untitled) - Hernández, J. G.; Juaristi, E. (J. Org. Chem., 2011)

Comprehensive Organic Synthesis - Hernández, J. G.; Avila-Ortiz, C. G.; Juaristi, E. (Useful Chemical Activation Alternatives in Solvent-Free Organic Reactions, 2014)

(untitled) - Hernández, J. G.; Ardila-Fierro, K. J.; Crawford, D.; James, S. L.; Bolm, C. (Green Chem., 2017)

(untitled) - Wiemann, L. O.; Nieguth, R.; Eckstein, M.; Naumann, M.; Thum, O.; Ansorge-Schumacher, M. B. (ChemCatChem, 2009)

(untitled) - Hernández, J. G.; Frings, M.; Bolm, C. (ChemCatChem, 2016)

(untitled) - Kleine, T.; Buendia, J.; Bolm, C. (Green Chem., 2013)

(untitled) - Calvaruso, G.; Clough, M. T.; Rinaldi, R. (Green Chem., 2017)

(untitled) - Hick, S. M.; Griebel, C.; Restrepo, D. T.; Truitt, J. H.; Buker, E. J.; Bylda, C.; Blair, R. G. (Green Chem., 2010)

(untitled) - Boissou, F.; Sayoud, N.; De Oliveira Vigier, K.; Barakat, A.; Marinkovic, S.; Estrine, B.; Jérôme, F. (ChemSusChem, 2015)

(untitled) - Rechulski, M. D. K.; Käldström, M.; Richter, U.; Schüth, F.; Rinaldi, R. (Ind. Eng. Chem. Res., 2015)

(untitled) - Chen, X.; Yang, H.; Zhong, Z.; Yan, N. (Green Chem., 2017)

(untitled) - Qian, Y.; Qiu, X.; Zhu, S. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Prinsen, P.; Narani, A.; Hartog, A. F.; Wever, R.; Rothenberg, G. (ChemSusChem, 2017)

(untitled) - Buono, P.; Duval, A.; Verge, P.; Averous, L.; Habibi, Y. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Zhao, X.; Huang, A.; Zhang, Y.; Yang, M.; Chen, D.; Huang, K.; Hu, H.; Huang, A.; Qin, X.; Feng, Z. (J. Appl. Polym. Sci., 2017)

(untitled) - Hulin, L.; Husson, E.; Bonnet, J.-P.; Stevanovic, T.; Sarazin, C. (Molecules, 2015)

(untitled) - Lohr, T. L.; Li, Z.; Marks, T. J. (ACS Catal., 2015)

(untitled) - Pan, X.; Kadla, J. F.; Ehara, K.; Gilkes, N.; Saddler, J. N. (J. Agric. Food Chem., 2006)

(untitled) - Qian, Y.; Qiu, X.; Zhu, S. (Green Chem., 2015)

(untitled) - Buendia, J.; Mottweiler, J.; Bolm, C. (Chem. – Eur. J., 2011)

(untitled) - Dabral, S.; Mottweiler, J.; Rinesch, T.; Bolm, C. (Green Chem., 2015)

(untitled) - Mottweiler, J.; Puche, M.; Räuber, C.; Schmidt, T.; Concepción, P.; Corma, A.; Bolm, C. (ChemSusChem, 2015)

(untitled) - Mottweiler, J.; Rinesch, T.; Besson, C.; Buendia, J.; Bolm, C. (Green Chem., 2015)

(untitled) - Dabral, S.; Hernández, J. G.; Kamer, P. C. J.; Bolm, C. (ChemSusChem, 2017)

(untitled) - Stergiou, P.-Y.; Foukis, A.; Filippou, M.; Koukouritaki, M.; Parapouli, M.; Theodorou, L. G.; Hatziloukas, E.; Afendra, A.; Pandey, A.; Papamichael, E. M. (Biotechnol. Adv., 2013)

(untitled) - Kirk, O.; Christensen, M. W. (Org. Process Res. Dev., 2002)

(untitled) - Xu, F.; Wang, J.; Liu, B.; Wu, Q.; Lin, X. (Green Chem., 2011)

(untitled) - Paravidino, M.; Hanefeld, U. (Green Chem., 2011)

(untitled) - Rahimi, A.; Azarpira, A.; Kim, H.; Ralph, J.; Stahl, S. S. (J. Am. Chem. Soc., 2013)